Diet Mate: A Personal Nutrition and Health Tracking App - Vineet Singh; Saurabh Singh (International Journal of Nutritions, 2025)
The rising prevalence of chronic health conditions, including obesity, diabetes, and hypertension, has become a significant global health challenge. These conditions are often linked to poor dietary habits, which makes diet management a critical component of disease prevention and management. Traditional dietary approaches, such as generic meal plans or standard consultations with nutritionists, often fail to address the unique and evolving needs of individuals, especially those with specific health concerns. To address this gap, this study explores the development and evaluation of a personalized diet management app that tailors meal plans to the unique needs of individuals based on their health conditions, dietary preferences, and goals.The app is designed to provide users with customized meal suggestions that promote healthy eating habits while also managing specific health conditions, such as diabetes, hypertension, and obesity. By integrating health data, such as blood sugar levels, blood pressure, and weight, the app offers real-time dietary recommendations that align with users' changing health metrics.Key findings from the study demonstrate significant health improvements among participants, including better blood sugar control for diabetic users and reduced blood pressure for those with hypertension. Additionally, users reported high levels of satisfaction, with many expressing appreciations for the app’s personalized approach. The study's results suggest that such personalized tools can be a valuable resource in managing chronic diseases, potentially leading to improved health outcomes and a better quality of life for users.
Keywords: Diet Mate; Health Tracking App; Meal Plan Algorithm; Personalized Meal Plans; UCD